Dynamic frontostriatal functional peak connectivity (in alcohol use disorder) - Gerchen, Martin Fungisai; Weiss, Franziska; Kirsch, Martina; Rentsch, Alena; Halli, Patrick; Kiefer, Falk; Kirsch, Peter (Human brain mapping, 2021)
Alcohol use disorder (AUD) is associated with changes in frontostriatal connectivity, but functional magnetic resonance imaging (fMRI) functional connectivity (FC) approaches are usually not adapted to these circuits. We developed a circuit-specific fMRI analysis approach to detect dynamic changes in frontostriatal FC inspired by medial-ventral-rostral to lateral-dorsal-caudal frontostriatal gradients originally identified in nonhuman primate tract-tracing data. In our PeaCoG (“peak connectivity on a gradient”) approach we use information about the location of strongest FC on empirical frontostriatal connectivity gradients. We have recently described a basic PeaCoG version with conventional FC, and now developed a dynamic PeaCoG approach with sliding-window FC. In resting state data of n = 66 AUD participants and n = 40 healthy controls we continue here the analyses that we began with the basic version. Our former result of an AUD-associated ventral shift in right orbitofrontal cortex PeaCoG is consistently detected in the dynamic approach. Temporospatial variability of dynamic PeaCoG in the left dorsolateral prefrontal cortex is reduced in AUD and associated with self-efficacy to abstain and days of abstinence. Our method has the potential to provide insight into the dynamics of frontostriatal circuits, which has so far been relatively unexplored, and into their role in mental disorders and normal cognition.
Gesehen am 09.06.2021